2016
DOI: 10.1007/s12040-015-0651-0
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variation of ocean heat content and tropical cyclone activity over the Bay of Bengal

Abstract: The upper ocean heat content up to 700 m depth (OHC 700) is an important climatic parameter required for atmospheric and oceanographic studies like a cyclone. In this study, therefore, an attempt has been made to examine the inter-decadal variations of tropical cyclone (TC) activity and OHC 700 over the Bay of Bengal (BOB) for the post-monsoon season (October-December) during 1955-2013 periods. The sea-surface temperature (SST), geopotential height at 500 hPa, low-level vorticity at 850 hPa, vertical wind shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Geopotential height denotes the actual height of the pressure surface above mean sea level and basically indicates the position of trough and ridge in the middle troposphere (500 hPa). Negative geopotential height anomalies (low heights) indicate the trough or cyclones at mid‐tropospheric level (Nath et al, ). Composite plots of 500 hPa geopotential heights anomalies clearly indicate the distinct large scale patterns with positive anomalies during El Niño and negative anomalies during La Niña years consistent with the below normal and above normal TCs frequency (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Geopotential height denotes the actual height of the pressure surface above mean sea level and basically indicates the position of trough and ridge in the middle troposphere (500 hPa). Negative geopotential height anomalies (low heights) indicate the trough or cyclones at mid‐tropospheric level (Nath et al, ). Composite plots of 500 hPa geopotential heights anomalies clearly indicate the distinct large scale patterns with positive anomalies during El Niño and negative anomalies during La Niña years consistent with the below normal and above normal TCs frequency (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…They found that the translational speed (TS) of cyclonic disturbances over the BoB ranged from 6.4 to 9.6 km h −1 over the first four decades , and over the recent decade (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), this has increased to 17.6 km h −1 . Nath et al (2016) have also studied decadal variations of ocean heat content and TC activity over the BoB during the 1955-2013 periods. According to Rajeevan et al (2013), epochal variation in the storm's atmospheric VWS anomalies and oceanic heat content contributed to more violent TCs occurring during the most recent epoch (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) than during the earlier epoch (1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992).…”
Section: Introductionmentioning
confidence: 99%
“…studies have indicated that during the past decades, the SST has been increasing in the World Ocean and individual ocean basins (Ting et al, 2009;Large and Yeager, 2012;Reid and Beaugrand, 2012;Krokos et al, 2019;Noori et al, 2019;Hereher, 2020;Pisano et al, 2020;Garcia-Soto et al, 2021;Al Senafi, 2022) and that the same has been happening for the OHC (Levitus et al, 2000;Willis et al, 2004;Nagamani et al, 2016;Nath et al, 2016;Cheng et al, 2017;Storto et al, 2019). Belkin (2009) performed a study on large marine ecosystems and suggested a rapid warming rate for the period 1982-2006, which was stronger in small marginal seas.…”
mentioning
confidence: 99%